PENENTUAN STRUKTUR KRISTAL AlMg2 ALLOY DENGAN DIFRAKSI NEUTRON - Ismul Hadi, Arif; Sumariyah, Sumariyah; Dahlan, M.; Mohtar, Mohtar (BERKALA FISIKA, 2011)
The determination of crystallography structure of AlMg2 alloy has been done by neutron diffraction. In fabrication process, it was addressed by rolling phases. The first by hot rolling with thickness follows: 8.35 mm; 7.00 mm; 5.6 mm; 2.60 mm; 1.65 mm ± 0.05 at  425 0C temperature extended by cold rolling: 1.65 mm to 1.30 mm ± 0,07 thickness at normal temperature. Counting of the data was started by activate of detector from 110 to 400 angle with 0.075 overstep and preset monitor count of 60,000 at 26 MW. Processing of the data using of microcomputer 16 bit NEC PC-9801 VM2. The results show that the AlMg2 alloy structure are FCC system with lattice parameter (a) = 4.0817 A0.   Keywords: AlMg2 alloy, neutron diffraction, and FCC